Efficacy and safety of tadalafil for the treatment of erectile dysfunction: results of integrated analyses - Brock, Gerald B; McMahon, Chris G; Chen, K K; Costigan, Timothy; Shen, Wei; Watkins, Vish; Anglin, Greg; Whitaker, Steve (The Journal of urology, 2002)
We conducted integrated analyses of the efficacy and safety of tadalafil, a potent, selective phosphodiesterase 5 inhibitor, for the treatment of erectile dysfunction. A total of 1,112 men with a mean age of 59 years (range 22 to 82) and mild to severe erectile dysfunction of various etiologies were randomized to placebo or tadalafil, taken as needed without food or alcohol restrictions, at fixed daily doses of 2.5 mg, 5 mg, 10 mg, or 20 mg up to a maximum of once daily [DOSAGE ERROR CORRECTED] in 5 randomized, double-blind, placebo controlled trials lasting 12 weeks. The 3 co-primary outcomes were changes from baseline in the erectile function domain of the International Index of Erectile Function and the proportion of "yes" responses to questions 2 and 3 of the Sexual Encounter Profile. Additional efficacy instruments included a Global Assessment Question. Compared with placebo, tadalafil significantly enhanced all efficacy outcomes. Patients receiving 20 mg. tadalafil experienced a significant mean improvement of 7.9 in International Index of Erectile Function erectile function domain score from baseline (p <0.001 versus placebo), 75% of intercourse attempts (Sexual Encounter Profile question 3, a secondary efficacy outcome) were successfully completed (p <0.001 versus placebo) and 81% reported improved erections at end point compared with 35% in the control group (p <0.001). Tadalafil was consistently efficacious across disease severities and etiologies, as well as in patients of all ages. Tadalafil was well tolerated, and headache and dyspepsia were the most frequent adverse events. Tadalafil was effective and well tolerated in this patient population.